Supported Nano-SiO2 H14[NaP5W30O110] Heteropolyacid: A Green and Reusable Catalyst in Oxidation of Aromatic Aldehydes - F. Bamoharram, Fatemeh; M. Heravi, Majid; Omidinia, Raheleh (Asian Journal of Chemistry, 2012)
H14[NaP5W30O110] is deposited on silica nanoparticles and used as recyclable heterogeneous catalysts in the oxidation of benzaldehydes to carboxylic acids both in thermal conditions and microwave irradiation. In catalytic reactions, the effects of various parameters such as catalyst amount, loading percentage and reaction time were examined. We found that the use of nano-SiO2-supported H14[NaP5W30O110] coupled to microwave irradiation allows a solvent- free, rapid (4-5 min) and high-yielding reaction. This catalyst can be easily recovered and reused for many times without a significant loss in its activity.